On mobile transaction processing in dynamically configurable mobile database communities - Brayner, Angelo; De Aguiar Moraes Filho, José (International journal of parallel, emergent and distributed systems, 2006)
The topology of a mobile ad hoc network (MANET) may change randomly and rapidly at an unpredictable time, since nodes are free to move arbitrarily. In such an environment, we may have a collection of autonomous, distributed, heterogeneous and mobile databases (denoted mobile database community (MDBC)). This paper describes an approach for controlling concurrency of mobile transactions executed in MDBCs. The proposed approach is based on the use of semantic knowledge to relax the notion of absolute transaction atomicity. Supported by this new concept of atomicity, we propose a new correctness criterion, denoted mobile semantic serializability, for the execution of concurrent transactions in MDBCs. The proposed correctness criterion provides a high degree of inter-transaction parallelism and ensures consistency of the mobile database.